Implementasi Metode Regionprops Untuk Mendeteksi Objek Image Fraktur Tulang - Nadilla Sarah Sinaga (Journal of Informatics Management and Information Technology, 2022)
Bone is one of the most important parts of the human body. The function of the bone itself is as a framework, a support for the human body and a place for muscles to attach, so that the body can move optimally. Not only that, some parts of the bones also have a function to protect other organs in the body. Such as the skull that serves to protect the brain from various kinds of impact from the outside, the arrangement of the ribs which serves to protect the lungs and so on. Regionprops method is a method used to measure a set of properties - properties of each region that has been labeled in the label matrix. A positive integer that is an element of the matrix corresponding to the corresponding region. This study uses the Regionprops method to detect an object of damage that is on a bone invoice. The application for detection of bone invoice object image results from Regionprops shows that the resolution produced by the detected image is different. The speed of the application to perform the image detection process depends on the pixel resolution and also depends on the specifications of the computer running the image detection application